Student success and retention: What’s academic skills got to do with it? - Ashton-Hay, Sally Ann; Doncaster, Naomi (Journal of Academic Language and Learning, 2021)
As the importance of student success and retention in higher education increases, the need for academic support is also crucial to assist the growing number of students from diverse backgrounds. This study assessed whether the attendance of students for an Academic Skills consultation made any difference in terms of performance, success, GPA, and attrition. Over 13,000 student consultations with Academic Skills in 2017, 2018 and 2019 were matched in the University Management Information System to allow derivation of metrics. The findings indicate that students who attended Academic Skills performed better than those who did not attend Academic Skills and the difference is greater for those who attended more consultations. Student GPA was also higher and more students completed their degree as a result. A recommendation is made for universities to strategically position and resource academic language and learning support services in order to enhance the student experience.